Implementation of A Village Fund Allocation Management for Sustainable Rural Development in Sigaluh Sub-District, Banjarnegara - Kurniawan, Agung; Primadata, Ankarlina Pandu; Lestari, Soraya Fajar Ayu; Putri, Ardila (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
Village governments are responsible for distributing village funds. This study aims to explain how village funds are managed to achieve sustainable development by allocating them to four sectors: village government, village development, community empowerment, and emergency disaster management. Effectiveness measurement indicators include goal achievement, integration, and adaptation to the results of achievements. Data was obtained from 14 villages in Sigaluh District, Banjarnegara Regency, and a qualitative method was used. The research was conducted through interview methods and literature studies on government reports on the allocation of village funds that each village has implemented. The results showed that the village funds in Sigaluh District were distributed in the four areas based on the community's priority needs that were agreed upon at Musrembang. The priority of the village government administration is to provide more effective and efficient services to the community. Village development focuses on physical and non-physical development, including increasing village road access and providing Posyandu assistance to reduce stunting. The allocation of funds in community empowerment is focused on the agriculture, fisheries, and UMKM sectors to support village food security. Emergency disaster management is focused on handling COVID-19 and disaster mitigation. Local village governments play important and crucialrole in sustainable development in rural areas as they control the implementation of various programs. The allocation of village funds in the Sigaluh sub-district is designed to be carried out with the principle of frugality, directed at achieving goals and benefits for the village community, and is well-controlled.